2019
DOI: 10.1080/13662716.2019.1650253
|View full text |Cite
|
Sign up to set email alerts
|

Identifying cooperation for innovation―a comparison of data sources

Abstract: The value of social network analysis is critically dependent on the comprehensive and reliable identification of actors and their relationships. We compare regional knowledge networks based on different types of data sources, namely, co-patents, copublications, and publicly subsidized collaborative R&D projects. Moreover, by combining these three data sources, we construct a multilayer network that provides a comprehensive picture of intraregional interactions. By comparing the networks based on the data sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 43 publications
0
13
0
3
Order By: Relevance
“…As noted by Broekel and Boschma, "firms' embeddedness in knowledge networks is crucial for their economic success" [28] (p. 3) and firms tend to acquire knowledge from various sources [14]. A number of studies highlight human resources [13,29,30] and the research system [31,32] as playing a pivotal role for firms' innovation performance. This set of studies argues that human resources (regarded, among others, as the knowledge or skills of workers) have a high potential for enhancing competitive advantage not only of firms, but also of regions and countries [10,29].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by Broekel and Boschma, "firms' embeddedness in knowledge networks is crucial for their economic success" [28] (p. 3) and firms tend to acquire knowledge from various sources [14]. A number of studies highlight human resources [13,29,30] and the research system [31,32] as playing a pivotal role for firms' innovation performance. This set of studies argues that human resources (regarded, among others, as the knowledge or skills of workers) have a high potential for enhancing competitive advantage not only of firms, but also of regions and countries [10,29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are strong arguments for regarding the research system as fundamental for knowledge diffusion among firms, universities and research organisations, which is likely to affect firms' innovation activities [6,27,40,41]. It has been observed that the research system plays a crucial role in external knowledge creation [13,14]. Following this, the existing literature shows the relevance of international scientific co-publications, the top 10% most cited publications, and foreign doctorate students for innovation performance of firms [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notwithstanding these merits, it is also widely acknowledged in the literature that patent data has its drawbacks, as some industries are more prone to patenting than others (e.g. Graf and Henning 2009), and patents represent only a partial picture of inventors' social networks in particular, and cooperation for innovation more generally (Fritsch, Titze, and Piontek 2020). Therefore, our analysis shows only a partial account on inter-regional collaborative knowledge production.…”
Section: Datamentioning
confidence: 90%
“…In economic geography, quantitative empirical studies investigating the processes of knowledge sourcing use mostly secondary data on patents, scientific publications, and R&D projects (Bettencourt, Lobo, and Strumsky 2007;Lobo and Strumsky 2008;Strumsky and Lobo 2015;Breschi and Lenzi 2016;Juhász and Lengyel 2017;Abbasiharofteh and Broekel 2020;. Although these studies have contributed a lot to the understanding of how firms create, maintain, and dissolve knowledge ties, more recently, scholars have called for the use of alternative firm-level databases to address unresolved research questions in economic geography (Duranton and Kerr 2018;Fritsch, Titze, and Piontek 2020). In this study, we build on the Mannheim Enterprise Panel (MUP) of 2019.…”
Section: Empirical Approach 41 Datamentioning
confidence: 99%